Pengaruh Promosi, Lokasi Dan Kualitas Pelayanan Terhadap Peningkatan Jumlah Anggota Pada KSPPS Bmt Mandiri Sejahtera Jawa Timur (Cabang Balongpanggang) - Retno, Alvira Dwi; Aslamiyah, Suaibatul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The increasingly rapid development of cooperatives means that competition is also increasing, therefore, in order to survive, cooperatives must pay attention of location, promotion and service quality so that they can attract potential customers. This research aims to determine the influence of location, promotion and service quality on increasing cooperative members with a population of KSPPS BMT Mandiri Sejahtera East Java cooperative members (Balongpanggang Branch). The sample consisted of 120 cooperative members who were selected using Yount's percentage theory. SPSS 23 software was used for data analysis and hypothesis testing. The research results show that location and service quality have a positive and significant effect on increasing of members at KSPPS BMT Mandiri Sejahtera East Java (Branch Balongpanggang). Meanwhile, the promotion variable has a positive and insignificant effect on increasing of members at the KSPPS BMT Mandiri Sejahtera East Java (Branch Balongpanggang).